Association of paternal MTHFR polymorphisms (C677T) with clinical outcomes in ICSI treatment - Wan, Yangyang; Liu, Wenjing; Xu, Bo; Jiang, Xiaohua; Hua, Juan (Frontiers in Endocrinology, 2022)
Purpose This study aims to investigate the association between paternal methylenetetrahydrofolate reductase (MTHFR) polymorphisms (C677T) and embryonic development, pregnancy, and neonatal outcomes in intracytoplasmic sperm injection (ICSI) treatment. Methods A total of 191 infertile men undergoing ICSI treatment at the Reproductive and Genetic Hospital, The First Affiliated Hospital of USTC, were recruited between January 2020 and June 2021. The MTHFR C677T polymorphism genotyping was evaluated in these male patients, and they were stratified into three groups according to genotyping results: Control (CC), heterozygote mutated (CT), and mutated homozygote (TT). In addition, we conducted a comparative analysis of embryonic development, pregnancy, and neonatal outcomes among these three groups. Results The embryonic development (including normal fertilization rate (80.14% vs. 83.06% vs. 85.10%; p = 0.37), high-quality embryo rate (45.26% vs. 43.69% vs. 46.04%; p = 0.72), blastocyst formation rate (42.47% vs. 43.18% vs. 39.38%; p = 0.62), implantation rate (42.47% vs. 36.25% vs. 41.22%; p = 0.62), and clinical pregnancy rate (64.71% vs. 58.75% vs. 66.67%; p = 0.59) were not comparable among these three groups. Moreover, no significant difference was observed in terms of pregnancy outcomes (including miscarriage rate (24.24% vs. 12.77% vs. 22.5%; p = 0.35) and live birth rate (49.02% vs. 51.25% vs. 51.66%; p = 0.96)). Additionally, no marked difference was observed in terms of neonatal outcome (including, preterm delivery rate (24% vs. 14.63% vs. 9.67%; p = 0.35), birth height (p = 0.75), birth weight (p = 0.35), neonatal sex (p = 0.48), gestational age at delivery (p = 0.24), Apgar score (p = 0.34), and birth defects (0% vs. 2% vs. 9%; p = 0.23) among the study groups. Conclusion The paternal MTHFR C677T polymorphism is not associated with embryo quality, pregnancy, or neonatal outcomes in ICSI treatment. Therefore, in our population, MTHFR polymorphisms do not provide helpful information in explaining ICSI failure.